Sublingual Administration of Sildenafil Oro-dispersible Film: New Profiles of Drug Tolerability and Pharmacokinetics for PDE5 Inhibitors - De Toni, Luca; De Rocco Ponce, Maurizio; Franceschinis, Erica; Dall’Acqua, Stefano; Padrini, Roberto; Realdon, Nicola; Garolla, Andrea; Foresta, Carlo (Frontiers in Pharmacology, 2018)
Objective. Type 5 phosphodiesterase inhibitors (PDE5i) are efficient drugs used for treatment of erectile dysfunction (ED); however, a large discontinuation rate due to major side effects is reported. The aim of this study was to evaluate the possible improvement of sildenafil (Sild) pharmacokinetics associated to the sublingual administration of the new available oro-dispersible film (ODF), compared to both the oro-dispersible tablet (ODT) and the film coated tablet (FCT) as original per os formulation. Methods. In vitro disaggregation test, dissolution test and permeation test in specific devices to estimate the trans-mucosal absorption. In vivo analysis of serum Sild levels, by HPLC-MS/MS, was performed in 20 patients with psychogenic ED receiving alternatively per os FCT or sublingual ODT or ODF, at an equal dosage (50 mg). Pharmacokinetic parameters of Sild and adverse drug reactions experienced after the dosing of each formulation were compared. Results. In vitro, ODF showed the highest time to disaggregation and an increased rate of permeation compared to both ODT and FCT (P=0,017 and P=0,008, respectively). In vivo, compared to both FCT and ODT, ODF showed a faster increase of serum Sild levels (serum levels at 15 min from dosing respectively: 2,24±1,4 ng/mL FCT, 0,5±0,3 ng/mL ODT and 13,5±9,1 ng/mL ODF; P<0,01 and P<0,05 vs ODF) together with a higher drug bioavailability within 60 minutes from dosing (relative AUC60min vs FCT respectively: 100,0±44,9% FCT, 183,8±75,4% ODT and 304,2±156,0% ODF). A trend towards lower peak serum levels was observed for ODF. Finally, ODF showed a lower prevalence of headache compared to FCT (1% vs 35%; P<0,05) and improved pattern of flushing and nasal congestion. Conclusion. Sublingual Sild oro-dispersible film improves the drug tolerability through a likely modified pharmacokinetic, suggesting a possible implication also in the clinical efficacy profile. Sublingual administration of oro-dispersible formulations may represent a strategy to ameliorate the adherence to therapy with PDE5i, particularly in patients discouraged by side effects.